Analysis of P5 Activities in Forming Cultural Character at the Seventh Grade Students of SMP N 1 Buay Pemuka Peliung - Nasyiatul Asiyah; Ainur Rohmah; Dwi Andriani (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This research aims to analyze the implementation of the Project for Strengthening the Pancasila Student Profile (P5) in shaping the cultural character of seventh-grade students at SMPN 1 Buay Pemuka Peliung. The primary focus of the research is to evaluate the forms of P5 activities, such as batik-making and folklore writing, and to identify the supporting and inhibiting factors in their implementation. The results show that the P5 activities have effectively helped students understand and appreciate local culture and enhanced teamwork skills through group activities. Overall, P5 has significantly contributed to make stronger cultural character among students, although challenges such as time constraints and limited resources were encountered.